2018
DOI: 10.1016/j.neurobiolaging.2018.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Mendelian adult-onset leukodystrophy genes in Alzheimer's disease: critical influence of CSF1R and NOTCH3

Abstract: Mendelian adult-onset leukodystrophies are a spectrum of rare inherited progressive neurodegenerative disorders affecting the white matter of the central nervous system. Among these, cerebral autosomal dominant and recessive arteriopathy with subcortical infarcts and leukoencephalopathy, cerebroretinal vasculopathy, metachromatic leukodystrophy, hereditary diffuse leukoencephalopathy with spheroids, and vanishing white matter disease present with rapidly progressive dementia as dominant feature and are caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 46 publications
3
26
0
Order By: Relevance
“…A previous study reported an association of AD with a distinct NOTCH3 mutation (p.R1231C) in a Turkish family 46 ; however, this variant was detected in only 1 affected member and there is conflicting information about its pathogenicity. 47 Sassi et al 48 tested the hypothesis that genes associated with mendelian adult-onset leukodystrophy are also associated with AD in a sample including 332 sporadic participants with AD and 676 controls and found a significant gene-based association with NOTCH3 , a result driven primarily by a common synonymous coding variant.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported an association of AD with a distinct NOTCH3 mutation (p.R1231C) in a Turkish family 46 ; however, this variant was detected in only 1 affected member and there is conflicting information about its pathogenicity. 47 Sassi et al 48 tested the hypothesis that genes associated with mendelian adult-onset leukodystrophy are also associated with AD in a sample including 332 sporadic participants with AD and 676 controls and found a significant gene-based association with NOTCH3 , a result driven primarily by a common synonymous coding variant.…”
Section: Discussionmentioning
confidence: 99%
“…The critical contribution of inflammation to Alzheimer’s disease pathogenesis has been further implicated by recent genome-wide association studies (GWAS), which highlight multiple immune-related genes in association with Alzheimer’s disease (Efthymiou and Goate, 2017), including the colony-stimulating factor 1 receptor ( CSF1R ) (Sassi et al , 2018). This evidence indicates that neuroinflammation and microglial activation are key drivers of Alzheimer’s disease pathology.…”
Section: Introductionmentioning
confidence: 99%
“…The brain pathology and symptoms of ALSP vary significantly between affected individuals and the disease has been misdiagnosed antemortem as various other dementias and neurodegenerative diseases. For example, Sassi et al 24 identified 3 likely pathogenic CSF1R mutations in a cohort of 465 lateonset Alzheimer's patients.…”
mentioning
confidence: 99%